2022
DOI: 10.1039/d2nr04320c
|View full text |Cite
|
Sign up to set email alerts
|

Anion-responsive self-assembled hydrogels of a phenylalanine–TREN conjugate allow sequential release of propranolol and doxorubicin

Abstract: Stimuli-responsive self-assembly and supramolecular hydrogels derived from peptide amphiphiles have opened exciting new avenues in biomedicine and drug delivery. Herein, we screened a series of phenylalanine-amphiphiles possessing polyamine and oxyethylene...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…While these methods are used to obtain specific structural data, they are often used in conjunction with additional techniques to allow full characterisation of a sample. These techniques can include but are not limited to NMR spectroscopy, 61 differential scanning calorimetry (DSC), 62 TEM, 63,64 AFM, SEM and Raman spectroscopy. 65…”
Section: Discussionmentioning
confidence: 99%
“…While these methods are used to obtain specific structural data, they are often used in conjunction with additional techniques to allow full characterisation of a sample. These techniques can include but are not limited to NMR spectroscopy, 61 differential scanning calorimetry (DSC), 62 TEM, 63,64 AFM, SEM and Raman spectroscopy. 65…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, Pradhan et al designed an amphiphilic molecule comprising of phenylalanine and tris(aminoethyl)amine (TREN), NapF-TREN. 74 Fig. 4 Ionic-responsive peptide-based hydrogels.…”
Section: Ionic-responsivementioning
confidence: 99%
“…Basak et al 58 used magnesium salts with different anions to complex with peptides and investigated the mechanical properties of the formed hydrogels, which showed that the storage modulus of the hydrogels decreased with increasing anion size. Pradhan et al 59 studied the interaction of anions with the amine residues of these peptide chains. When the anions were HPO 4 2− and SO 4 2− , the hydrogels remained stable, and when the anions were H 2 PO 4 − or HSO 4 − , the hydrogels were rapidly destroyed and the storage modulus decreased.…”
Section: Factors Influencing the Formation Of Peptide Hydrogelsmentioning
confidence: 99%